2019
DOI: 10.3390/ijerph16152660
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Provision of Health Services and Barriers to Treatment for Chronic Diseases among Syrian Refugees in Turkey: A Review of Literature and Stakeholder Interviews

Abstract: Background: While Turkey hosts the largest number of Syrian refugees, the provision of health services for chronic disease among Syrian refugees in Turkey has been inadequate and understudied. This paper explores Turkish healthcare policies surrounding Syrian refugees’ access to health services for chronic diseases. Methods: We conducted a literature review and supplementary stakeholder interviews to evaluate the provision of chronic health services and the most common barriers to healthcare access among Syria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 34 publications
0
54
0
Order By: Relevance
“…Qualitative research on Syrian refugees in Jordan found emotional distress to be the most frequently highlighted trigger for the incidence or exacerbation of non-communicable disease [51]. While Syrians registered for temporary protection have the right to free primary and secondary health care in Turkey, language barriers and a limited understanding of the health system limit access to these services [52]. Integrating evidence-based mental health interventions, such as cognitive behavioural therapy, into primary and community care could increase the recognition of psychological symptoms, reduce stigma, and improve the availability of services.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative research on Syrian refugees in Jordan found emotional distress to be the most frequently highlighted trigger for the incidence or exacerbation of non-communicable disease [51]. While Syrians registered for temporary protection have the right to free primary and secondary health care in Turkey, language barriers and a limited understanding of the health system limit access to these services [52]. Integrating evidence-based mental health interventions, such as cognitive behavioural therapy, into primary and community care could increase the recognition of psychological symptoms, reduce stigma, and improve the availability of services.…”
Section: Discussionmentioning
confidence: 99%
“…The majority ( n = 37, 82%) involved populations living in or fleeing from conflict-affected countries while only eight were of populations affected by natural disasters ( Ramachandran, 2005 ; Chan and Kim, 2011 , 2010 ; Hung et al , 2013 ; Sun et al , 2013 ; Martinez et al , 2015 ; Mobula et al , 2016 ; Adrega et al , 2018 ). Among the studies from conflict-affected contexts, almost half ( n = 18, 49%) concerned the protracted displacement of Palestinian populations served by UNRWA in their five fields of operation within the MENA region ( Yusef, 2000 ; Mousa et al , 2010 ; Khader et al , 2012a,b, 2013 , 2014a,b ,c; Alabed et al , 2014 ; Saadeh et al , 2015 ; Shahin et al , 2015 ; Santoro et al , 2016 ; Radwan et al , 2017 ; Damiri et al , 2018 ; Saleh et al , 2018a,b ,c; Abu Kishk et al , 2019 ); 10 concerned Syrian refugees in the host countries Jordan, Lebanon, and Turkey ( Kallab, 2015 ; Collins et al , 2017 ; Doocy et al , 2017 ; Hyatt, 2017 ; Sethi et al , 2017 ; Elliott et al , 2018 ; Alawa et al , 2019 ; Kayali et al , 2019 ; McNatt et al , 2019 ; Boulle et al , 2019b ); three described forcibly displaced Iraqis in Iraq and Jordan ( Mateen et al , 2012 ; Istepanian et al , 2014 ; Baxter et al , 2018 ); five concerned protracted conflicts in Mali, Democratic Republic of Congo (DRC), or Myanmar (Burma) and one described an acute conflict setting in the Philippines ( Besancon et al , 2015 ; Murphy et al , 2017 ; Naing and Bakker, 2018 ; <...>…”
Section: Resultsmentioning
confidence: 99%
“…Seven papers (15%) presented research intervention studies, including two implementation studies measuring the impact of an NCD intervention, and three others using mixed methods for evaluation. Three studies used a qualitative approach of semi-structured interviews with patients or key stakeholders that focused on barriers to NCD care ( Baxter et al , 2018 ; Alawa et al , 2019 ; McNatt et al , 2019 ). Baxter et al (2018) and McNatt et al (2019) specifically elicited the patient perception of NCD care.…”
Section: Resultsmentioning
confidence: 99%
“…e interviewed administrators in our study complemented the perspective of health care professionals. Bureaucratic aspects and having to navigate a different health care system represent barriers to ensuring continuity of health care and were also observed outside Germany [43,49].…”
Section: Discussionmentioning
confidence: 99%